Effect of Intermittent Spray Pyrolysis on the Characteristics of Fluorine-Doped Tin Oxide Conductive Glass for Dye Sensitized Solar Cell - Isdiriayani Nurdin; Pramujo Widiatmoko; Hary Devianto; Anastasia Yuandy; Rendy Rendy (Dept. of Chemical Engineering, Diponegoro University, 2019)
One of dye sensitized solar cell’s (DSSC) component is conductive glass, a transparent glass substrate covered with semiconductor oxide, usually fluorine-doped tin oxide (FTO). An economic and scalable method used to deposit the FTO film is spray pyrolysis. A research conducted by Fukano et al. (2004) showed that introducing intermittence in spray pyrolysis using batch atomizer improves the glass’ characteristics. This research aims to observe the effect of intermittence on spray pyrolysis method using nebulizer. A compressor nebulizer and hotplate were used, where the glass’ surface temperature reached 300oC. Transmittance, conductance, morphology and composition of the glasses produced were analyzed. Deposition time and intermittence were varied. Variation of time were 5; 7.5; 10; 16; and 39 minutes. Deposition time of 7.5 minutes showed the highest figure of merit (FOM) of 7.83×10-3 Ω-1. Intermittence was performed by turning the nebulizer off during deposition, with varying period and amount of intermittence. Periods of intermittence were varied for 10, 20, and 30 seconds, and amounts of intermittence were varied 1, 2, and 3 times. Variation of 3 intermittences at 20 seconds each resulted in the highest FOM of 19.29×10-3 Ω-1. DSSC’s efficiency built using produced conductive glass are 1.9×10-4 % and 5.5×10-4 %.